INTEGRATION OF REFUGEE PROTECTION PRINCIPLES IN THE ENFORCEMENT OF CRIMINAL LAW ON HUMAN SMUGGLING IN INDONESIA: A STUDY OF THE ROHINGYA ETHNIC SMUGGLING CASE - Mita Syahfitri Panjaitan; Rika Kurniaty; Faizin Sulistiofaizinl@ub.ac.id (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The increasing influx of Rohingya refugees into Indonesia has created complex legal issues as it involves human smuggling crimes, immigration law, as well as refugee protection and human rights. Rohingya refugees, who are stateless persons and have been subjected to prolonged persecution in Myanmar, are often targeted by transnational organized crime networks that facilitate their illegal cross-border movement. This situation raises questions regarding the extent to which Indonesian criminal law is capable of addressing human smuggling crimes involving Rohingya refugees, integrating international refugee protection principles, and providing adequate protection for refugees as victims.This study is a normative legal research employing conceptual, statutory, and philosophical approaches. The legal materials consist of primary, secondary, and tertiary sources obtained through library research and internet-based documentation, which are then analyzed using deductive, inductive, systematic, interpretative, and comparative methods, as well as case-based analysis of legislation and court decisions related to the smuggling of Rohingya refugees.The findings show that Indonesian criminal law has established a relatively comprehensive normative framework through the Immigration Law, the Indonesian Penal Code, and the ratification of the United Nations Convention Against Transnational Organized Crime (UNTOC) and its Protocol against the Smuggling of Migrants. In addition, the principles of non-penalization, non-refoulement, and humanitarian protection have been substantively integrated into law enforcement practices, although Indonesia has not yet ratified the 1951 Refugee Convention and its 1967 Protocol.This research proposes a victim-oriented criminal law model through the integration of international refugee protection principles, recognition of restitution as a right of refugee victims, and the provision of safe, decent, and humane shelter, in order to achieve legal certainty, substantive justice, and the protection of human dignity.